A comparative study of epithelial cell proliferation between the odontogenic keratocyst, orthokeratinized odontogenic cyst, dentigerous cyst, and ameloblastoma - Thosaporn W. (2014)
OBJECTIVES: The aim of the present study was to compare the proliferation index of the epithelial cells between odontogenic keratocysts (OKC), orthokeratinized odontogenic cysts (OOC), dentigerous cysts (DC), and ameloblastomas. MATERIALS AND METHODS: The proliferation index, employing a novel cell proliferation marker IPO-38, was studied by the immunohistochemical technique in 10 OKC, seven OOC, eight DC and 10 ameloblastomas. RESULTS: The ameloblastoma had no higher labeling index (LI) of IPO-38 than the OKC (P = 0.910) but had higher LI than the OOC (P = 0.001) and DC (P = 0.000); the OKC had higher LI than the OOC (P = 0.002) and DC (P = 0.000); and the OOC had higher LI than the DC (P = 0.011). IPO-38-positive cells in the OKC and OOC were located principally in the suprabasal cell layers while the ameloblastoma were found in the peripheral portion in particularly, the follicular and plexiform types. CONCLUSION: These findings support previous studies that the proliferation indices are useful in predicting the different biological behavior of the odontogenic lesions and the OKC should be regarded as a benign tumor rather than simply an odontogenic cyst.